(untitled) (Contemporary Mathematics, 2023)
The randomness of a sequence plays an important role in cryptography like deciding the key, encryption and decryption algorithms. The sequences obtained by permutation polynomials over the finite fields have different properties which are used as random number generators. In the present paper, we have checked the randomness of sequence of numbers obtained from permutation polynomials over prime finite fields using different non-parametric statistical tests.